Rethinking teacher education in Liberia’s rural teacher training institutes: key challenges and strategic solutions - Gabriel M. Kennedy (Discover Education)
Abstract Teacher education is essential for improving Liberia’s education system, particularly in rural areas where qualified teachers are scarce. Liberia’s Rural Teacher Training Institutes (RTTIs) play a crucial role in addressing this shortage, yet several challenges undermine their effectiveness. This study identified key barriers to effective teacher preparation in RTTIs and explored how targeted reforms can enhance educational outcomes. A narrative review was conducted using Guskey’s professional development model as the theoretical framework. The findings revealed that misaligned curricula prevent trainees from developing essential 21st-century skills. Financial shortfalls further limit access to modern teaching resources and practicum opportunities, while weak policy implementation and inadequate professional development for teacher educators reduce instructional quality. These gaps create a disconnect between theoretical knowledge and practical classroom application, leaving preservice teachers unprepared for modern teaching demands. Recommendations include realigning the curriculum to integrate modern teaching competencies, expanding practicum experience through stronger partnerships, and increasing financial support to improve teacher training infrastructure. Enhanced policy coordination and ongoing professional development for teacher educators are also essential for improving instructional quality. This study contributes to the field by identifying key barriers in Liberia’s teacher training programs and applying Guskey’s model to explain how these challenges undermine the effectiveness of Liberia’s RTTIs. It proposed targeted reforms to enhance teacher preparation and improve educational outcomes in resource-constrained settings. Implementing these reforms will strengthen RTTIs’ capacity to prepare 21st-century teachers, thereby improving student learning and supporting Liberia’s educational development.